Depletion of Scleraxis-lineage cells during tendon healing transiently impairs multi-scale restoration of tendon structure during early healing. - Antonion Korcari; Samantha Muscat; Elizabeth McGinn; Mark R Buckley; Alayna E Loiselle (PLoS ONE, 2022)
Tendons are composed of a heterogeneous cell environment, with Scleraxis-lineage (ScxLin) cells being the predominant population. Although ScxLin cells are required for maintenance of tendon homeostasis, their functions during tendon healing are unknown. To this end, we first characterized the spatiotemporal dynamics of ScxLin cells during tendon healing, and identified that the overall ScxLin pool continuously expands up to early remodeling healing phase. To better define the function of ScxLin cells during the late proliferative phase of healing, we inducibly depleted ScxLin cells from day 14-18 post-surgery using the Scx-Cre; Rosa-DTR mouse model, with local administration of diphtheria toxin inducing apoptosis of ScxLin cells in the healing tendon. At D28 post-surgery, ScxLin cell depleted tendons (DTRScxLin) had substantial impairments in structure and function, relative to WT, demonstrating the importance of ScxLin cells during tendon healing. Next, bulk RNAseq was utilized to identify the underlying mechanisms that were impaired with depletion and revealed that ScxLin depletion induced molecular and morphological stagnation of the healing process at D28. However, this stagnation was transient, such that by D56 tendon mechanics in DTRScxLin were not significantly different than wildtype repairs. Collectively, these data offer fundamental knowledge on the dynamics and roles of ScxLin cells during tendon healing.